The Structure and Magnetic Properties of Sm2Fe17Cx Compounds Prepared from Ball-Milled Mixtures of Sm2Fe17 and Carbon Nanotubes or Graphite - Vladislav A. Mikheev; Igor G. Bordyuzhin; Mikhail V. Gorshenkov; Elena S. Savchenko; Irina V. Dorofievich; Igor V. Shchetinin (Metals, 2024)
The processing route of Sm2Fe17 carbides is shorter than that of nitrides, which can potentially be used for cost-effective mid-performance magnets’ production. The magnetic properties of Sm2Fe17Cx compounds can be controlled at the annealing step, which allows them to be used for a variety of applications. In this work, X-ray diffraction (XRD) analysis, Mössbauer spectroscopy, scanning and transmission electron microscopy (SEM, TEM) and vibrating sample magnetometry (VSM) were used for characterization of the structure and magnetic properties of Sm2Fe17Cx compounds. The powder samples were prepared by high-energy ball milling of Sm2Fe17 mixtures with carbon nanotubes (CNT) or graphite with subsequent annealing. The formation of Sm2Fe17Cx compounds after annealing was followed by the formation of α-Fe and amorphous Sm2O3. The hyperfine field values of Fe atoms of all the Sm2Fe17 lattice sites increased by 12% on average after annealing that was caused by carbon diffusion. The coercivity of the samples peaked after annealing at 375 °C. The samples with CNT demonstrated an increase of up to 14% in coercivity and 5% in specific remanence in the range of 250–375 °C annealing temperatures.